Enhancing the wearablity and accessibility of illuminated POF garment. Issue 2 (5th September 2019) - Bai, Vera Ziqian; Tan, Jeanne; Chen, Amy; Ge, Lan
Abstract : Purpose: The purpose of this paper is to develop an illuminated polymeric optical fibre (POF) garment – the LUMI jacket – with accessibility and wearability improvements. This paper demonstrates how wearable technology can be seamlessly integrated into daily life. Design/methodology/approach: An interdisciplinary approach involving design and technological techniques was adopted. Both garment design approaches and textile technologies were used to optimise the performance of a POF jacket. A group of tactile sensors was developed to create an easy-to-access interactive function. A POF fabric sample and garment were washed and examined to prove that a POF garment could be made part of a domestic laundry routine. Findings: As a result, an illuminated POF garment – the LUMI jacket with textile-based switches – was created. Compared with current POF garments, the LUMI jacket's wearability and accessibility were highly improved. Originality/value: This project explored an unobstructive POF-illuminated garment to address the functional and wearable barriers to adoption. The interaction between wearer and garment is accessible. Electronics and textile touch sensors were seamlessly integrated into garment. Washability of POF garment was proved. This research explores how e-textiles can fit into everyday life.